2014
DOI: 10.1007/s13369-014-1349-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ductile Fracture Models on Load Bearing Capacity of a Dented Aluminum Pipe Subjected to Internal Pressure

Abstract: In this work, three ductile fracture models based on different mechanical models namely Wilkins et al. (W), improved Johnson-Cook (J-C) and Xue and Wierzbicki (X-W) are introduced in the elastic-plastic finite element analysis to obtain the load bearing capacity of a dented aluminum pipe subjected to internal pressure loading. The target dent depth is considered as an indication of the load bearing capacity of the aluminum pipe with internal pressure under indentation process. Different combination of paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Several common burst pressure methods, usually described as a function of pipe diameter, pipe wall thickness, pipe material, and other parameters, have been studied for thermoplastic pipes, and the corresponding design criteria have been carefully analyzed [30]. Three ductile fracture models were proposed to obtain the burst pressure of a dented aluminum pipe and were verified using FEA by S. Jafari et al [31]. A simplified method based on multi-dimensional analysis was proposed for the analysis of the ultimate water pressure bearing capacity for large-caliber water supply pipes [32].…”
Section: Other 35%mentioning
confidence: 99%
See 1 more Smart Citation
“…Several common burst pressure methods, usually described as a function of pipe diameter, pipe wall thickness, pipe material, and other parameters, have been studied for thermoplastic pipes, and the corresponding design criteria have been carefully analyzed [30]. Three ductile fracture models were proposed to obtain the burst pressure of a dented aluminum pipe and were verified using FEA by S. Jafari et al [31]. A simplified method based on multi-dimensional analysis was proposed for the analysis of the ultimate water pressure bearing capacity for large-caliber water supply pipes [32].…”
Section: Other 35%mentioning
confidence: 99%
“…The power exponential constitutive model, as shown in Figure 5, has significant advantages in describing the nonlinear behavior of materials from plastic deformation to failure [37]. When the Tresca and von Mises yield criterion are used in material plasticity analysis, many studies have confirmed that the initial yield and post-yielding occur between those two theories' predictions [28,31]. To describe this plastic yield behavior more accurately, a new yield model, the ASSY criterion for isotropic hardening materials, was introduced and applied to burst pressure determination [36].…”
Section: Stress-strain Relationship Of Pvcmentioning
confidence: 99%
“…This equation has been widely used [11][12][13] and included in several commercial finiteelement software types; this is mainly due to the reduced number of constants that it used and the separation of the hardening, temperature, and strain rate effects. It was then applied to model the strain rate sensitivity mainly for metallic alloys as for titanium [14,15], copper [16], aluminum [17,18], and steel [19][20][21][22] alloys.…”
Section: Introductionmentioning
confidence: 99%